A single substance germanium / Ti3C2T x MXene electrode and its preparation method and application
By using additive-free element germanium/Ti3C2TxMXene electrodes in sodium ion batteries, the combination of element germanium nanoparticles and Ti3C2TxMXene nanosheets is used to solve the impact of additives on energy density and specific capacity in existing batteries, achieving high cycling performance and good low-temperature performance.
Patent Information
- Application Number
- CN202210664885.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2022-06-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-06-13
AI Technical Summary
The additives used in existing lithium-ion batteries do not contribute to energy density and specific capacity, and affect the cycling and low-temperature performance of the battery. Especially in the application of sodium ion batteries, the preparation of single germanium electrodes needs to be improved to improve their performance.
An additive-free elemental germanium/Ti3C2TxMXene electrode was used, which was prepared by mixing and uniformly coating on copper foil, which was prepared by drying in a vacuum drying box.
The high cycle performance and good low-temperature performance of sodium ion batteries were achieved. The first discharge reversible capacity reached 300 ~ 374 mAh g-1 at a current density of 100 mA g-1. The capacity retention rate reached 57% ~ 71% after 100 cycles, and it showed high charge and discharge capacity and good cycle performance at a temperature of -20 oC.
Smart Images

Figure CN116053413B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy materials, and specifically relates to a single substance germanium / Ti 3 C 2 T x MXene electrode and its preparation method and application. Background Art
[0002] Lithium-ion batteries are widely used in daily life due to their high specific capacity, high energy density, no memory function, and green environmental protection. However, with the emergence of portable electronic products and the rapid development of electric vehicles with long driving range, people's demand for lithium resources is also increasing. At the current development speed, the lithium element, which was originally not abundant on the surface, will soon be exhausted in the foreseeable future. Metallic sodium, which has the most similar chemical and physical properties to lithium, has become the object of research, and research on sodium-ion batteries is also developing rapidly in the field of energy storage.
[0003] The negative electrode material is the core factor affecting the capacity of sodium-ion batteries. Germanium has the advantages of low sodium storage platform and high theoretical capacity, making it one of the excellent negative electrode materials. In order to ensure the normal operation of the negative electrode material, additives such as conductive agents and binders are usually added when preparing the electrode. However, these additives not only do not contribute to the energy density of the battery, but also affect the specific capacity of the battery to a certain extent. Therefore, it is necessary to provide an improved technical solution for the preparation of single-element germanium electrodes.
[0004] In the past decade, the new two-dimensional carbide MXene has been widely used in the field of electrochemical energy storage and is one of the excellent candidate electrode materials. 3 C 2 T x MXene nanosheets have high metal-like conductivity and unique clay properties, and are expected to be used as conductive agents and binders for electrodes. Summary of the invention
[0005] The purpose of the present invention is to provide a single substance germanium / Ti without additives 3 C 2 T x MXene electrodes, their preparation methods and applications ensure the cycle performance and low-temperature performance of sodium-ion batteries.
[0006] To achieve the above object, the present invention provides a single substance germanium / Ti 3 C 2 T x MXene electrode, the single element germanium / Ti 3 C 2 T x MXene electrodes use single-element germanium nanoparticles as active materials, Ti3 C 2 T x MXene nanosheets act as both a binder and a conductive agent.
[0007] The single substance germanium / Ti of the present invention 3 C 2 T x The preparation method of MXene electrode is to use single-element germanium nanoparticles as active material and Ti 3 C 2 T x MXene nanosheets are used as both a binder and a conductive agent. The two are mixed in a certain mass ratio to form a uniform viscous paste, which is evenly coated on the copper foil and dried in a vacuum drying oven to obtain a single-element germanium / Ti 3 C 2 T x MXene electrodes.
[0008] The single substance germanium / Ti of the present invention 3 C 2 T x The specific steps of the preparation method of MXene electrode are as follows:
[0009] (1) Preparation of single-element germanium nanoparticles;
[0010] (2) Preparation of Ti 3 C 2 T x MXene nanosheets;
[0011] (3) Using single-element germanium nanoparticles as active materials and Ti 3 C 2 T x MXene nanosheets are used as both a binder and a conductive agent. After the two are mixed, deionized water is used as a dispersant and ultrasonic dispersion is performed under a high-purity nitrogen atmosphere to form a uniform viscous paste. The viscous paste is evenly coated on a clean copper foil and dried in a vacuum drying oven to obtain Ti 3 C 2 T x MXene nanosheets.
[0012] Furthermore, the preparation method of the single-element germanium nanoparticles in step (1) is as follows: 2 As germanium source, NaBH 4 As a reducing agent, single-element germanium nanoparticles were prepared by freeze drying; specifically, 1 g GeO 2 Disperse into 10 mL of deionized water and add 2 mL of ammonia solution to make GeO 2 After the mixture was completely dissolved, slowly add dropwise 1.8 g NaBH 410 mL aqueous solution was reacted at room temperature for 24 h, centrifuged and washed with deionized water, and the obtained product was freeze-dried at a vacuum temperature (-40 ~ -50 o C) and vacuum dried for 2 days to obtain single-element germanium nanoparticles.
[0013] Furthermore, step (2) Ti 3 C 2 T x The preparation method of MXene nanosheets is as follows: 3 AlC 2 As raw material, Ti was prepared by mild LiF+HCl etching method. 3 C 2 T x MXene nanosheets; specifically as follows: 0.98 g LiF was dispersed in 10 mL concentrated hydrochloric acid, and 1 g Ti was slowly added 3 AlC 2 , as for 36 o C water bath and stirred vigorously for 24 h. After the reaction was completed, the mixture was centrifuged and washed with distilled water until pH>6. The resulting precipitate was a multilayer Ti 3 C 2 T x The precipitate was dispersed in 20 mL of distilled water, ultrasonicated on ice for 1 h under nitrogen atmosphere, centrifuged at 3500 rpm for 1 h, and the upper suspension was taken, which was the minority layer of Ti 3 C 2 T x MXene nanosheets.
[0014] Furthermore, in step (3), the elemental germanium nanoparticles and Ti 3 C 2 T x The mass ratio of MXene nanosheets is 5:5 ~ 8:2.
[0015] Furthermore, in step (3), the drying temperature is 120 o C, drying time is 15 h.
[0016] The single substance germanium / Ti of the present invention 3 C 2 T x Application of MXene electrode as negative electrode of sodium ion battery. Specifically, the copper foil coated with slurry is punched into a circular electrode sheet with a diameter of 14 mm by a punching machine, which is used as the negative electrode of sodium ion battery.
[0017] Furthermore, at 100 mA g -1 The reversible capacity is as high as 374 mAh g at a current density of -1 , the capacity retention rate reached 71% after 100 cycles.
[0018] Furthermore, -20 o C, at 100 mA g -1 At a current density of 1.38 W, the first discharge capacity is 132 mAhg -1 After 100 cycles, the reversible charge capacity of the material can still reach 83 mAh g -1 , the capacity retention rate is 62%.
[0019] A single substance germanium / Ti of the present invention 3 C 2 T x MXene electrodes are characterized by:
[0020] 1) No additives such as adhesives and conductive agents.
[0021] 2) Germanium nanoparticles as active material, Ti 3 C 2 T x MXene is used as a conductive binder and as a negative electrode material for sodium-ion batteries.
[0022] Beneficial effects of the present invention: The single-substance germanium nanoparticles obtained by the present invention are used as active materials, Ti 3 C 2 T x MXene nanosheets as binders and conductors are used as negative electrodes for sodium-ion batteries at 100 mA g -1 The current density was 300 ~ 374 mAh g -1 The first discharge reversible capacity. During the return process, Ti 3 C 2 T x MXene nanosheets provide high conductivity to ensure good electrical contact between the electrodes. Their high mechanical flexibility can effectively buffer the volume expansion of elemental germanium during the charge and discharge process, ensuring good cycle stability. After 100 cycles, the capacity retention rate is 57% to 71%, showing high charge and discharge capacity and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The single substance germanium / Ti of Example 1 of the present invention 3 C 2 T x XRD pattern of MXene electrode.
[0024] Figure 2 The single substance germanium / Ti of Example 1 of the present invention 3 C 2 T xScanning electron microscopy image of a MXene electrode.
[0025] Figure 3 The single substance germanium / Ti of Example 2 of the present invention 3 C 2 T x Charge and discharge curves of MXene electrode at room temperature.
[0026] Figure 4 The single substance germanium / Ti of Example 5 of the present invention 3 C 2 T x MXene electrode at -20 o Charge and discharge curves in C environment.
[0027] Figure 5 This is the charge and discharge curve of the single-substance germanium nanoparticle electrode under room temperature conditions of Example 6 of the present invention. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.
[0029] Example 1
[0030] This example shows single-element germanium / Ti 3 C 2 T x The preparation method of MXene electrode is as follows:
[0031] 1) GeO 2 As germanium source, NaBH 4 As a reducing agent, single-element germanium nanoparticles were prepared by freeze drying. 2 Disperse into 10 mL of deionized water and add 2 mL of ammonia solution to make GeO 2 Completely dissolved. Slowly add dropwise 1.8 g NaBH 4 10 mL aqueous solution was reacted at room temperature for 24 h, centrifuged and washed with deionized water, and the obtained product was freeze-dried at a vacuum temperature (-40 ~ -50 o C) and vacuum dried for 2 days to obtain single-element germanium nanoparticles.
[0032] 2) Ti 3 AlC 2 As raw material, Ti was prepared by mild LiF+HCl etching method. 3 C 2 T xMXene nanosheets. Specifically, 0.98 g LiF was dispersed in 10 mL concentrated hydrochloric acid, and 1 g Ti was slowly added. 3 AlC 2 , as for 36 o C water bath and stirred vigorously for 24 h. After the reaction was completed, the mixture was centrifuged and washed with distilled water until pH>6. The resulting precipitate was a multilayer Ti 3 C 2 T x The precipitate was dispersed in 20 mL of distilled water, ultrasonicated on ice for 1 h under nitrogen atmosphere, centrifuged at 3500 rpm for 1 h, and the upper suspension was taken, which was the minority layer of Ti 3 C 2 T x MXene nanosheets.
[0033] 3) Using single-element germanium nanoparticles as active materials and Ti 3 C 2 T x MXene nanosheets were used as both a binder and a conductive agent. The two were mixed in a mass ratio of 5:5, and deionized water was used as a dispersant. Ultrasonic dispersion was performed for 30 min in a high-purity nitrogen atmosphere to form a uniform viscous paste, which was evenly coated on a clean copper foil and dried in a vacuum oven at 120 °C. o C for 15 h.
[0034] 4) Use a punching machine to punch the copper foil coated with the slurry into a circular electrode sheet with a diameter of 14 mm, which will serve as the negative electrode of the sodium ion battery. Figure 1 As shown in the figure, X-ray powder diffraction shows that the obtained single-element germanium nanoparticles are single-element germanium in cubic phase, corresponding to the JCPDS card number (04-0545), and no impurity peaks appear, indicating that the product has high purity. Figure 2 The scanning electron microscope image shows that the particle size of the single-element germanium nanoparticles is 20 ~ 60 nm.
[0035] Sodium metal sheets were used as counter and reference electrodes, glass fiber (GF / C) was used as the diaphragm, and 1 M NaCF 3 SO 3 The diglyme solution was used as the electrolyte, and the battery assembly was carried out in a glove box filled with Ar. The battery charge and discharge performance was tested at room temperature using the LandBT2013A charge and discharge instrument produced by Wuhan Landian. -1 At a current density of 3 C 2 T x The first discharge capacity of MXene electrode is 300 mAh g -1After 100 cycles, the reversible charge capacity of the material can still reach 194 mAh g -1 , the capacity retention rate is 65%.
[0036] Example 2
[0037] This example shows single-element germanium / Ti 3 C 2 T x The preparation method of MXene electrode is as follows:
[0038] 1) GeO 2 As germanium source, NaBH 4 As a reducing agent, single-element germanium nanoparticles were prepared by freeze drying. 2 Disperse into 10 mL of deionized water and add 2 mL of ammonia solution to make GeO 2 Completely dissolved. Slowly add dropwise 1.8 g NaBH 4 10 mL aqueous solution was reacted at room temperature for 24 h, centrifuged and washed with deionized water, and the obtained product was freeze-dried at a vacuum temperature (-40 ~ -50 o C) and vacuum dried for 2 days to obtain single-element germanium nanoparticles.
[0039] 2) Ti 3 AlC 2 As raw material, Ti was prepared by mild LiF+HCl etching method. 3 C 2 T x MXene nanosheets. Specifically, 0.98 g LiF was dispersed in 10 mL concentrated hydrochloric acid, and 1 g Ti was slowly added. 3 AlC 2 , as for 36 o C water bath and stirred vigorously for 24 h. After the reaction was completed, the mixture was centrifuged and washed with distilled water until pH>6. The resulting precipitate was a multilayer Ti 3 C 2 T x The precipitate was dispersed in 20 mL of distilled water, ultrasonicated on ice for 1 h under nitrogen atmosphere, centrifuged at 3500 rpm for 1 h, and the upper suspension was taken, which was the minority layer of Ti 3 C 2 T x MXene nanosheets.
[0040] 3) Using single-element germanium nanoparticles as active materials and Ti 3 C 2 T xMXene nanosheets were used as both a binder and a conductive agent. The two were mixed in a mass ratio of 6:4, and deionized water was used as a dispersant. Ultrasonic dispersion was performed for 30 min in a high-purity nitrogen atmosphere to form a uniform viscous paste, which was evenly coated on a clean copper foil and dried in a vacuum oven at 120 °C. o C for 15 h.
[0041] 4) The copper foil coated with the slurry is punched into a circular electrode sheet with a diameter of 14 mm using a punching machine, which serves as the negative electrode of the sodium ion battery.
[0042] The sodium ion battery was assembled in the same manner as in Example 1, and the battery charge and discharge performance was tested at room temperature using a LandBT2013A charge and discharge instrument produced by Wuhan Landian. Figure 3 As shown, at 100 mA g -1 At a current density of 3 C 2 T x The first discharge capacity of the MXene electrode is 341 mAh g -1 After 100 cycles, the reversible charge capacity of the material can still reach 235 mAh g -1 , the capacity retention rate is 69%.
[0043] Example 3
[0044] This example shows single-element germanium / Ti 3 C 2 T x The preparation method of MXene electrode is as follows:
[0045] 1) GeO 2 As germanium source, NaBH 4 As a reducing agent, single-element germanium nanoparticles were prepared by freeze drying. 2 Disperse into 10 mL of deionized water and add 2 mL of ammonia solution to make GeO 2 Completely dissolved. Slowly add dropwise 1.8 g NaBH 4 10 mL aqueous solution was reacted at room temperature for 24 h, centrifuged and washed with deionized water, and the obtained product was freeze-dried at a vacuum temperature (-40 ~ -50 o C) and vacuum dried for 2 days to obtain single-element germanium nanoparticles.
[0046] 2) Ti 3 AlC 2 As raw material, Ti was prepared by mild LiF+HCl etching method. 3 C 2 Tx MXene nanosheets. Specifically, 0.98 g LiF was dispersed in 10 mL concentrated hydrochloric acid, and 1 g Ti was slowly added. 3 AlC 2 , as for 36 o C water bath and stirred vigorously for 24 h. After the reaction was completed, the mixture was centrifuged and washed with distilled water until pH>6. The resulting precipitate was a multilayer Ti 3 C 2 T x The precipitate was dispersed in 20 mL of distilled water, ultrasonicated on ice for 1 h under nitrogen atmosphere, centrifuged at 3500 rpm for 1 h, and the upper suspension was taken, which was the minority layer of Ti 3 C 2 T x MXene nanosheets.
[0047] 3) Using single-element germanium nanoparticles as active materials and Ti 3 C 2 T x MXene nanosheets were used as both a binder and a conductive agent. The two were mixed in a mass ratio of 7:3, and deionized water was used as a dispersant. Ultrasonic dispersion was performed for 30 min in a high-purity nitrogen atmosphere to form a uniform viscous paste, which was evenly coated on a clean copper foil and dried in a vacuum oven at 120 °C. o C for 15 h.
[0048] 4) The copper foil coated with the slurry is punched into a circular electrode sheet with a diameter of 14 mm using a punching machine, which serves as the negative electrode of the sodium ion battery.
[0049] The sodium ion battery was assembled in the same manner as in Example 1, and the battery charge and discharge performance was tested at room temperature using a LandBT2013A charge and discharge instrument produced by Wuhan Landian. -1 At a current density of 3 C 2 T x The first discharge capacity of the MXene electrode is 365 mAh g -1 After 100 cycles, the reversible charge capacity of the material can still reach 250 mAh g -1 , the capacity retention rate is 68%.
[0050] Example 4
[0051] This example shows single-element germanium / Ti 3 C 2 T x The preparation method of MXene electrode is as follows:
[0052] 1) GeO 2As germanium source, NaBH 4 As a reducing agent, single-element germanium nanoparticles were prepared by freeze drying. 2 Disperse into 10 mL of deionized water and add 2 mL of ammonia solution to make GeO 2 Completely dissolved. Slowly add dropwise 1.8 g NaBH 4 10 mL aqueous solution was reacted at room temperature for 24 h, centrifuged and washed with deionized water, and the obtained product was freeze-dried at a vacuum temperature (-40 ~ -50 o C) and vacuum dried for 2 days to obtain single-element germanium nanoparticles.
[0053] 2) Ti 3 AlC 2 As raw material, Ti was prepared by mild LiF+HCl etching method. 3 C 2 T x MXene nanosheets. Specifically, 0.98 g LiF was dispersed in 10 mL concentrated hydrochloric acid, and 1 g Ti was slowly added. 3 AlC 2 , as for 36 o C water bath and stirred vigorously for 24 h. After the reaction was completed, the mixture was centrifuged and washed with distilled water until pH>6. The resulting precipitate was a multilayer Ti 3 C 2 T x The precipitate was dispersed in 20 mL of distilled water, ultrasonicated on ice for 1 h under nitrogen atmosphere, centrifuged at 3500 rpm for 1 h, and the upper suspension was taken, which was the minority layer of Ti 3 C 2 T x MXene nanosheets.
[0054] 3) Using single-element germanium nanoparticles as active materials and Ti 3 C 2 T x MXene nanosheets were used as both a binder and a conductive agent. The two were mixed in a mass ratio of 8:2, and deionized water was used as a dispersant. Ultrasonic dispersion was performed for 30 min in a high-purity nitrogen atmosphere to form a uniform viscous paste, which was evenly coated on a clean copper foil and dried in a vacuum oven at 120 °C. o C for 15 h.
[0055] 4) The copper foil coated with the slurry is punched into a circular electrode sheet with a diameter of 14 mm using a punching machine, which serves as the negative electrode of the sodium ion battery.
[0056] The sodium ion battery was assembled in the same manner as in Example 1, and the battery charge and discharge performance was tested at room temperature using a LandBT2013A charge and discharge instrument produced by Wuhan Landian. -1 At a current density of 3 C 2 T x The first discharge capacity of the MXene electrode is 374 mAh g -1 After 100 cycles, the reversible charge capacity of the material can still reach 192 mAh g -1 , the capacity retention rate is 51%.
[0057] Example 5
[0058] This example shows single-element germanium / Ti 3 C 2 T x The preparation method of MXene electrode is as follows:
[0059] 1) GeO 2 As germanium source, NaBH 4 As a reducing agent, single-element germanium nanoparticles were prepared by freeze drying. 2 Disperse into 10 mL of deionized water and add 2 mL of ammonia solution to make GeO 2 Completely dissolved. Slowly add dropwise 1.8 g NaBH 4 10 mL aqueous solution was reacted at room temperature for 24 h, centrifuged and washed with deionized water, and the obtained product was freeze-dried at a vacuum temperature (-40 ~ -50 o C) and vacuum dried for 2 days to obtain single-element germanium nanoparticles.
[0060] 2) Ti 3 AlC 2 As raw material, Ti was prepared by mild LiF+HCl etching method. 3 C 2 T x MXene nanosheets. Specifically, 0.98 g LiF was dispersed in 10 mL concentrated hydrochloric acid, and 1 g Ti was slowly added. 3 AlC 2 , as for 36 o C water bath and stirred vigorously for 24 h. After the reaction was completed, the mixture was centrifuged and washed with distilled water until pH>6. The resulting precipitate was a multilayer Ti 3 C 2 T xThe precipitate was dispersed in 20 mL of distilled water, ultrasonicated on ice for 1 h under nitrogen atmosphere, centrifuged at 3500 rpm for 1 h, and the upper suspension was taken, which was the minority layer of Ti 3 C 2 T x MXene nanosheets.
[0061] 3) Using single-element germanium nanoparticles as active materials and Ti 3 C 2 T x MXene nanosheets were used as both a binder and a conductive agent. The two were mixed in a mass ratio of 6:4, and deionized water was used as a dispersant. Ultrasonic dispersion was performed for 30 min in a high-purity nitrogen atmosphere to form a uniform viscous paste, which was evenly coated on a clean copper foil and dried in a vacuum oven at 120 °C. o C for 15 h.
[0062] 4) The copper foil coated with the slurry is punched into a circular electrode sheet with a diameter of 14 mm using a punching machine, which serves as the negative electrode of the sodium ion battery.
[0063] The sodium ion battery was assembled in the same manner as in Example 1, and a LandBT2013A type charge and discharge instrument produced by Wuhan Landian was used at -20 o The battery charging and discharging performance is tested at a temperature of C. Figure 4 As shown, at 100 mA g -1 At a current density of 3 C 2 T x The first discharge capacity of the MXene electrode is 132 mAh g -1 After 100 cycles, the reversible charge capacity of the material can still reach 83 mAh g -1 , the capacity retention rate is 62%.
[0064] Example 6
[0065] The preparation method of the single-substance germanium nanoparticle comparison electrode of this embodiment is as follows:
[0066] 1) GeO 2 As germanium source, NaBH 4 As a reducing agent, single-element germanium particles were prepared by freeze drying. 2 Disperse into 10 mL of deionized water and add 2 mL of ammonia solution to make GeO 2 Completely dissolved. Slowly add dropwise 1.8 g NaBH 410 mL aqueous solution was reacted at room temperature for 24 h, centrifuged and washed with deionized water, and the obtained product was freeze-dried at a vacuum temperature (-40 ~ -50 o C) and vacuum dried for 2 days to obtain single-element germanium nanoparticles.
[0067] 2) Elemental germanium nanoparticles were used as active materials, traditional sodium carboxymethyl cellulose (CMC) as a binder, and commercial acetylene black as a conductive agent. The three were mixed in a mass ratio of 8:1:1, and deionized water was used as a dispersant. Ultrasonic dispersion was performed for 30 min under a high-purity nitrogen atmosphere to form a uniform viscous paste, which was evenly coated on a clean copper foil and dried in a vacuum oven at 120 °C. o C for 15 h.
[0068] 3) The copper foil coated with the slurry is punched into a circular electrode sheet with a diameter of 14 mm using a punching machine, which serves as the negative electrode of the sodium ion battery.
[0069] The sodium ion battery was assembled in the same manner as in Example 1, and the battery charge and discharge performance was tested at room temperature using a LandBT2013A charge and discharge instrument produced by Wuhan Landian. Figure 5 As shown, at 100 mA g -1 At a current density of 1.3 Å, the first discharge capacity of the single-substance germanium nanoparticle comparison electrode prepared in this example is 447 mAh g -1 After 100 cycles, the reversible charge capacity of the material decreased to 98 mAh g -1 , the capacity retention rate is 22%.
[0070] In the performance tests of the six embodiments, single-element germanium / Ti 3 C 2 T x MXene electrodes are shown to be superior to existing commercially available graphene negative electrode materials.
[0071] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A single element germanium / Ti3C2T x The application of MXene electrode as the negative electrode of sodium ion battery is characterized by: The single substance germanium / Ti3C2T x MXene electrodes use single-element germanium nanoparticles as active materials, Ti3C2T x MXene nanosheets are used as both a binder and a conductive agent. The preparation method is as follows: single-element germanium nanoparticles are used as active materials, Ti3C2T x MXene nanosheets act as both a binder and a conductor, bonding single-element germanium nanoparticles and Ti3C2T x The MXene nanosheets were mixed to form a uniform viscous paste, which was evenly coated on the copper foil and dried in a vacuum oven to obtain single-element germanium / Ti3C2T x MXene electrodes.
2. The use according to claim 1, characterized in that: at 100 mA g -1 The reversible capacity is as high as 374 mAh g at a current density of -1 , the capacity retention rate reached 71% after 100 cycles.
3. The use according to claim 1, characterized in that: -20 o C, at 100 mA g -1 At a current density of 1.34 W, the first discharge capacity is 132 mAh g -1 After 100 cycles, the reversible charge capacity of the material can still reach 83 mAh g -1 , the capacity retention rate is 62%.
4. The use according to claim 1, characterized in that: Germanium / Ti3C2T x The preparation method of MXene electrode, the specific steps are as follows: (1) Preparation of single-element germanium nanoparticles; (2) Preparation of Ti3C2T x MXene nanosheets; (3) Using single-element germanium nanoparticles as active materials and Ti3C2T x MXene nanosheets are used as both a binder and a conductive agent. After the two are mixed, deionized water is used as a dispersant and ultrasonic dispersion is performed in a high-purity nitrogen atmosphere to form a uniform viscous paste. The viscous paste is evenly coated on a clean copper foil and dried in a vacuum drying oven to obtain a single-element germanium / Ti3C2T x MXene electrodes.
5. The use according to claim 4, characterized in that: Step (1) The method for preparing elemental germanium nanoparticles is as follows: GeO2 is used as a germanium source and NaBH4 is used as a reducing agent, and elemental germanium nanoparticles are prepared by freeze drying; specifically, 1 g of GeO2 is dispersed in 10 mL of deionized water, 2 mL of ammonia solution is added to completely dissolve the GeO2, 10 mL of an aqueous solution containing 1.8 g of NaBH4 is slowly added drop by drop, reacted at room temperature for 24 h, centrifuged and washed with deionized water, and the obtained product is dried in a freeze dryer under vacuum and low temperature conditions for 2 days to obtain elemental germanium nanoparticles.
6. The use according to claim 4, characterized in that: Step (2) Ti3C2T x The preparation method of MXene nanosheets is as follows: Ti3AlC2 is used as raw material and a mild LiF+HCl etching method is used to prepare Ti3C2T x MXene nanosheets; specifically as follows: 0.98 g LiF was dispersed in 10 mL concentrated hydrochloric acid, 1 g Ti3AlC2 was slowly added, and placed at 36 o C water bath with strong stirring for 24 h. After the reaction, centrifuge and wash with distilled water until pH > 6. The resulting precipitate is multilayer Ti3C2T x The precipitate was dispersed in 20 mL of distilled water, ultrasonicated on ice for 1 h under nitrogen atmosphere, and centrifuged at 3500 rpm for 1 h. The upper suspension was the Ti3C2T x MXene nanosheets.
7. The use according to claim 4, characterized in that: In step (3), the single element germanium nanoparticles and Ti3C2T x The mass ratio of MXene nanosheets is 5:5 ~ 8:
2.
8. The use according to claim 4, characterized in that: The drying temperature in step (3) is 120 o C, drying time is 15 h.
Citation Information
Patent Citations
Two-dimensional transition metal carbide (nitride)-nano silicon granular composite material as well as preparation and application thereof
CN107394180A